Feasibility, safety, and preliminary efficacy of intermittent theta burst stimulation combined with task-oriented training in subacute stroke: A pilot randomized controlled trial. - Rida, Fatima; Feng, Yali; Zhou, Yi; Tan, Botao; Zhang, An; Yu, Lehua (Journal of Back & Musculoskeletal Rehabilitation, 2026)
Background and Purpose: Upper limb motor impairment after stroke is a leading cause of long-term disability. This single-center pilot randomized controlled trial (RCT) evaluated the safety, feasibility, and preliminary efficacy of intermittent theta-burst stimulation (iTBS) combined with task-oriented training (TOT) for upper limb rehabilitation. iTBS, a non-invasive brain stimulation technique, may enhance recovery when paired with task-oriented training (TOT), particularly in the subacute phase of heightened neuroplasticity. Methods: Twenty-nine patients with subacute stroke were randomized into three groups: (1) iTBS + TOT (n = 10), (2) sham iTBS + TOT (n = 9), and (3) traditional physiotherapy (n = 10). All underwent a 4-week intervention. Primary outcomes were safety and feasibility. Secondary outcomes included motor impairment (Fugl-Meyer Assessment for Upper Extremity, FMA-UE), functional independence (Modified Barthel Index, MBI), and neurological deficit (National Institutes of Health Stroke Scale, NIHSS), assessed at baseline, week 2, and week 4. Results: Twenty-nine participants completed the trial without any adverse events, and one participant from Group 2 discontinued early due to discharge. At week 4, the iTBS + TOT group showed greater improvements in FMA-UE (22.9 points vs. 3.6 and 10.2; p = 0.013; p = 0.013), NIHSS (3.0 vs 6.6; p = 0.009), and MBI (90.7 vs 51.4; p < 0.001) compared with controls, indicating potential functional benefits. Conclusions: This exploratory pilot RCT suggests that combining iTBS with TOT is safe and feasible, with preliminary evidence supporting its potential to improve upper limb recovery in subacute stroke. However, these findings should be interpreted with caution and validated in larger, adequately powered trials.